Land-Use Scenario Modeling Using Remote Sensing and Cellular Automata and Its Impact on the Drought Hazard at the Sub-catchment Area Level - Suryanta Junjungan Tua Sitio; Novandi Rizky Prasetya; Michelle Talisia Sugiarto; Aditya Nugraha Putra (Green Engineering Society, 2026)
Rapid land-use change in upland watersheds alters hydrological processes and increases drought vulnerability. The Upper Brantas and Kali Konto sub-watersheds in East Java serve as important rainfall catchment and water storage areas, yet ongoing land conversion has progressively reduced their capacity to regulate water availability. However, the implications of future land-use trajectories for drought hazards at the sub-catchment scale remain insufficiently understood. This study aims to analyze land-use dynamics, simulate future land-use change, and evaluate alternative land-use planning scenarios to assess their potential influence on drought hazard distribution. Multi-temporal land-use data from 2017, 2019, 2021, and 2025 were analyzed using remote sensing, and future land-use patterns were projected for 2030 using the Artificial Neural Network–Cellular Automata–Markov (ANN–CA–Markov) model. The simulated land-use distribution was then evaluated under Regional Spatial Planning (RSP) and Land Capability Classification (LCC) scenarios to examine their implications for drought hazards. The results showed a substantial decline in natural forest from 12,600.35 ha (31.4%) in 2017 to 9,975.70 ha (24.9%) in 2025—a reduction of more than 20%—accompanied by the expansion of plantation systems, dryland farming, and built-up areas. Under the 2030 Business-as-Usual (BAU) scenario, moderate drought hazard areas increased from 44.0% to approximately 50.2% of the watershed area. Among the evaluated scenarios, the Land Capability Classification (LCC)-based planning approach showed the greatest potential to mitigate drought risk, reducing high drought hazard areas from 25.1% under the BAU scenario to 15.2%. These findings highlight the importance of integrating land capability considerations into spatial planning to support drought-resilient watershed management.